2011
DOI: 10.2754/avb201180030249
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malassezia pachydermatis in dogs with suspected Malassezia dermatitis or otitis in Slovakia

Abstract: The aim of the study was to evaluate the prevalence of yeast Malassezia pachydermatis in dogs from Slovakia in relation to different predisposition factors (sex, age, body localisation, hair type, and season). Samples of ear swabs (58) and dermal swabs (131) from 147 dogs with clinical symptoms of suspected yeast dermatitis and/or otitis, were examined between June 2005 to June 2007. Relatively higher prevalence of M. pachydermatis was found in samples taken from males (45.2%) than in females (35.2%), and in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In the current study, males were found to be more susceptible to Malassezia, the prevalence in males was 60% against 40% in females, these findings are in complete agreement with the findings of Conkova et al, (2011) and Seetha et al, 2018. However, the results contradict the findings of Nardoni et al, 2004 who advocated no significant difference in the prevalence in both the sexes. The skewing of the incidence towards the males could be attributed to the fact that androgen triggers greater production of sebum Conkova et al, (2011) which predisposes the males to latent infection with Malassezia.…”
Section: Sex Wise Prevalencesupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, males were found to be more susceptible to Malassezia, the prevalence in males was 60% against 40% in females, these findings are in complete agreement with the findings of Conkova et al, (2011) and Seetha et al, 2018. However, the results contradict the findings of Nardoni et al, 2004 who advocated no significant difference in the prevalence in both the sexes. The skewing of the incidence towards the males could be attributed to the fact that androgen triggers greater production of sebum Conkova et al, (2011) which predisposes the males to latent infection with Malassezia.…”
Section: Sex Wise Prevalencesupporting
confidence: 88%
“…Both the sexes were found to be equally affected by Malassezia. The incidences are known to peak in summers due to high temperature of the tropical region Patterson and Frank (2002) while in the temperate climate the cases peak in the autumn Conkova et al, (2011). The prevalence was found to be highest in the age group of 1-3 years Girao et al, (2006).…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence findings based on sex was not very significant, maybe it need more sample and data analysis. Because according Conkova et al (2011), male dogs tend to be more susceptible to Malassezia infection than female dogs. The cause is the presence of androgen hormones in male dogs that increase sebum production, so the risk of fungal infection will rise.…”
Section: Penicillium Speciesmentioning
confidence: 99%
“…Malassezia pachydermatis is commonly involved in canine otitis externa [1,2]. Changes in the microenvironment and defective host immunity seem to be associated with Malassezia overgrowth [3].…”
Section: Introductionmentioning
confidence: 99%